2010
DOI: 10.1103/physrevb.81.174416
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NiO spin orientation on the magnetic anisotropy of the Fe film in epitaxially grown Fe/NiO/Ag(001) and Fe/NiO/MgO(001)

Abstract: Single crystalline Fe/NiO bilayers were epitaxially grown on Ag(001) and on MgO(001), and investigated by Low Energy Electron Diffraction (LEED), Magneto-Optic Kerr Effect (MOKE), and X-ray Magnetic Linear Dichroism (XMLD). We find that while the Fe film has an in-plane magnetization in both Fe/NiO/Ag(001) and Fe/NiO/MgO (001)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 20 publications
3
34
0
Order By: Relevance
“…Multiferroics research [9] relies on the coupling of ferroelectric and magnetic polarization vectors, which is usually not strong enough. Lattice mismatching can provide a fine method to tune the AFM strain and modify the magneto-crystalline anisotropy of the AFM film [10][11][12][13]. As a good example, the AFM spins in a NiO film prefer the in-plane direction if grown on Ag(001) with compressed strain, but align along the out-of-plane direction when grown on MgO(001) with tensile strain [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiferroics research [9] relies on the coupling of ferroelectric and magnetic polarization vectors, which is usually not strong enough. Lattice mismatching can provide a fine method to tune the AFM strain and modify the magneto-crystalline anisotropy of the AFM film [10][11][12][13]. As a good example, the AFM spins in a NiO film prefer the in-plane direction if grown on Ag(001) with compressed strain, but align along the out-of-plane direction when grown on MgO(001) with tensile strain [10].…”
Section: Introductionmentioning
confidence: 99%
“…Lattice mismatching can provide a fine method to tune the AFM strain and modify the magneto-crystalline anisotropy of the AFM film [10][11][12][13]. As a good example, the AFM spins in a NiO film prefer the in-plane direction if grown on Ag(001) with compressed strain, but align along the out-of-plane direction when grown on MgO(001) with tensile strain [10]. The AFM spin orientation of CoO films grown on MgO(001) and MnO(001) can also be tuned either in-plane or out-of-plane by varying the film strain [11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, FM hysteresis loop measurements of the Fe layer support the fact that the NiO spins have an in-plane direction in Fe/NiO/Ag(001) and an out-of-plane direction in Fe/NiO/MgO(001) [15]. Despite this progress, a continuous SRT from in-plane to out-ofplane directions has never been realized in an AFM thin film.…”
mentioning
confidence: 98%
“…The lattice mismatching method employs a fine tuning of the AFM strain to modify the magnetocrystalline anisotropy of the AFM thin film [11]. A promising system in the latter approach are epitaxial NiO/Ag and NiO/MgO thin films as NiO grows compressed on Ag(001) and in tensile strain on MgO (001) (a Ag =4.086Å < a NiO =4.176Å < a MgO =4.212Å) [15]. It was shown that epitaxial NiO films prefer an in-plane spin direction near the Ag interface and an out-of-plane spin direction near the MgO interface [12].…”
mentioning
confidence: 99%
“…In order to explain the exchange-coupling-induced anisotropies, different mechanisms have been proposed, such as collinear coupling at the spin-uncompensated interface, 2 non-collinear (spin-flop) coupling 12 originating from spin frustration, 13 etc. Usually, such exchange-coupling-induced anisotropy is attributed to the interaction between FM spins and AFM spins at the interface, and the importance of interfacial spin coupling has been realized and well-studied in many FM/AFM systems, such as Fe/CoO, [14][15][16] Fe/NiO, [17][18][19] and Co/FeMn. 20,21 However, discussions on the anisotropy are mostly based on the measurement of the coercivity field H C , which is also proportional to 1/d FM .…”
Section: Introductionmentioning
confidence: 99%